ANALYSIS FACTORS ASSOCIATED WITH INTEREST OF FAMILY PLANNING ACCEPTORS USING IUD IN KEUDE PANGA VILLAGE PANGA SUBDISTRICT - Rahmi, Nuzulul (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2017)
Research indicates that the choice of IUD contraceptive method especially in Indonesia during the last few years tends to decrease the demand. These factors include: physical, psychological, socio-cultural and religious factors, level of education, knowledge, environment, economy, needs, service tariff, and support of husband / family. The purpose of this study was to analyze the factors related to the interests of family planning acceptors using the IUD in Keude Panga Village Panga District 2017. This study was analytic, with cross sectional approach, the population in this study were all KB acceptor in Keude Panga Village, Panga Subdistrict totaling 175 people. Sampling technique is done by quota sampling, the number of samples obtained 35 people. Data was collected on May 13th until 26th of May 2017. Data analysis was done by using Chi-Square Test with 95% significance limit (P <0,05).The result of the research shows that there is correlation between mothers knowledge level with KB acceptor interest in using IUD with P value = 0.027, there is relation between economic level of family with KB acceptor interest in using IUD with value P = 0,001. There is relationship between husband support with KB acceptor interest in using IUD with value P = 0,007, there is relation between social culture with KB acceptor interest in using IUD with value P = 0,009. The conclusion in this study there is a meaningful relationship between knowledge, family economic level, husband support and social culture with the interest of KB acceptors who use IUD. Suggestions Expected for the development of science so that the results of this study can be used as a reference in the development of better science and to conduct further research on contraceptives in the womb.Keywords: Knowledge, Education, Economic Level, Husband Support,Â Socio-CultureÂ